Play and art as therapy with a child of divorce : a case study - Breen, Claire (Centre for Educational Research, 2023)
This case study aims to provide a description' and analysis of the therapeutic use of play and art with the child of divorce. The focus is the therapeutic process which facilitated the resolution of the themes of divorce and promoted the child's psychosocial development. The use of drawings during the assessment phase provided a deeper understanding of her experience of divorce. Client-centred play therapy complemented by art therapy facilitated the resolution of the divorce issues. The case material illustrates the use of play and art as therapeutic mediums as well as. the themes of divorce and the process of psychosocial development. The art material was analysed according to the research base used by the following contributors: Kramer (1958, 1971, 1979); Rubin (1977); Hammer (1954); Machover (1957); Goodenough (1928); Koppitz (1968); and Burns and Kaufman (1971). Plates of the child's work have been included. Each therapy session was described and analysed in terms of the themes.of divorce (Gardner, 1976; Mendell, 1983) and the child's psychosocial development (Erikson, 1963; Hamachek, 1988). The child's progress through the therapeutic process was· analysed according to Moustakas' (1955) Levels of Emotional Process. The findings were that the difficulties during the child's Trust Stage had predisposed her to later life adjustment problems. The stress of the divorce during her Initiative Stage resulted in her regressing to the Autonomy Stage which contributed to her difficulties with control and her emotional lability and fluctuating scholastic performance. The case study was written for professional people interested in child development ·with the aim of providing an understanding of the child's experience of divorce and its effects on the child's psychosocial development. By aiming to integrate m6re play and art into children's activities at home, in schools, hospitals and clinics, children will have the opportunity to optimise their own development.